2017
DOI: 10.1016/j.micinf.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of regulatory T cells augments induction of protective immune responses by influenza virus-like particles in aged mice

Abstract: Elderly humans over 65 years old are at great risk to pathogenesis by influenza virus infection. However, although influenza vaccines provide effective protection in healthy young adults, protection of elderly adults is substantially lower even with a good match between the vaccine and the circulating influenza virus. To gain insight of the underlying mechanism for the reduced immunogenicity of influenza vaccines in the aged population, we investigated immunogenicity of influenza virus-like particle vaccines i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In general, Treg function is activated in the elderly, 14 which reduces the effectiveness of influenza virus and varicella‐zoster virus (VZV) vaccines. 15 , 16 Moreover, the lower number of Tregs are also implicated in autoimmune diseases such as immune thrombocytopenia or transfusion‐related acute lung injury. 17 , 18 However, there are very few reports on the effect of Tregs on COVID‐19 vaccines, as aforementioned.…”
Section: Resultsmentioning
confidence: 99%
“…In general, Treg function is activated in the elderly, 14 which reduces the effectiveness of influenza virus and varicella‐zoster virus (VZV) vaccines. 15 , 16 Moreover, the lower number of Tregs are also implicated in autoimmune diseases such as immune thrombocytopenia or transfusion‐related acute lung injury. 17 , 18 However, there are very few reports on the effect of Tregs on COVID‐19 vaccines, as aforementioned.…”
Section: Resultsmentioning
confidence: 99%
“…Along these lines, another study in aged patients showed that non-responder individuals to influenza vaccination have a higher frequency of Treg as well as a higher inflammatory status compared to responders ( 128 ). Depletion of Treg with anti-CD25 treatment prior to influenza infection protected against lethal viral challenge in aged mice ( 129 ). In another study, responders to influenza vaccination showed a higher frequency of Treg compared to non-responders, together with an elevated frequency of early differentiated CD4 + T cells and lower proportion of memory CD4 + cells ( 130 ).…”
Section: Treg Homeostasis and Function In Agingmentioning
confidence: 99%
“…If there are too many Treg cells, the antiviral immunity and vaccination efficiency mediated by effector T cells and B cells may be suppressed, resulting in reduced inhibition of viral replication in the elderly; whereas, if Treg cells are insufficient in the inflammatory lung, the excessive immune reaction-induced tissue damage could be detrimental. Utilizing anti-CD25 to block Treg cell function has been demonstrated to augment protective immune responses to influenza virus-like particles in aged mice [ 128 ]. Induced Treg (iTreg) cells can be generated via transforming growth factor- β (TGF-β), while blocking TGF-β signaling impedes the conversion of CD4 T cells into iTreg cells and thereby facilitates immune responses abrogated by Treg suppression [ 129 ].…”
Section: How Can We Sufficiently Restore Antiviral Immunity and Immentioning
confidence: 99%